Examining implicit metacognition in 3.5-year-old children: an eye-tracking and pupillometric study - Paulus, Markus; Proust, Joelle; Sodian, Beate (Frontiers in Psychology, 2013)
The current study examined early signs of implicit metacognitive monitoring in 3.5-year-old children. During a learning phase children had to learn paired associates. In the test phase, children had to perform a recognition task and choose the correct associate for a given target among four possible answers. Subsequently, children’s explicit confidence judgments and their fixation time allocation at the confidence scale were assessed. Analyses showed that explicit confidence judgments did not differ for remembered compared to non-remembered items. In contrast, children’s fixation patterns on the confidence scale were affected by the correctness of their memory, as children looked longer to high confidence ratings when they correctly remembered the associated item. Moreover, analyses of pupil size revealed pupil dilations for correctly remembered, but not incorrectly remembered items. The results converge with recent behavioral findings that reported evidence for implicit metacognitive memory monitoring processes in 3.5-year-old children. The study suggests that implicit metacognitive abilities might precede the development of explicit metacognitive knowledge.